5-HT2C receptor perturbation has bidirectional influence over instrumental vigour and restraint - Härmson, O; Grima, LL; Panayi, MC; Husain, M; Walton, ME (Springer, 2021)
The serotonin (5-HT) system, particularly the 5-HT2C receptor, has consistently been implicated in behavioural control. However, while some studies have focused on the role 5-HT2C receptors play in regulating motivation to work for reward, others have highlighted its importance in response restraint. To date, it is unclear how 5-HT transmission at this receptor regulates the balance of response invigoration and restraint in anticipation of future reward. In addition, it remains to be established how 5-HT2C receptors gate the influence of internal versus cue-driven processes over reward-guided actions. To elucidate these issues, we investigated the effects of administering the 5-HT2C receptor antagonist SB242084, both systemically and directly into the nucleus accumbens core (NAcC), in rats performing a Go/No-Go task for small or large rewards. The results were compared to the administration of d-amphetamine into the NAcC, which has previously been shown to promote behavioural activation. Systemic perturbation of 5-HT2C receptors—but crucially not intra-NAcC infusions—consistently boosted rats’ performance and instrumental vigour on Go trials when they were required to act. Concomitantly, systemic administration also reduced their ability to withhold responding for rewards on No-Go trials, particularly late in the holding period. Notably, these effects were often apparent only when the reward on offer was small. By contrast, inducing a hyperdopaminergic state in the NAcC with d-amphetamine strongly impaired response restraint on No-Go trials both early and late in the holding period, as well as speeding action initiation. Together, these findings suggest that 5-HT2C receptor transmission, outside the NAcC, shapes the vigour of ongoing goal-directed action as well as the likelihood of responding as a function of expected reward.